Effect of Aqueous Methanolic Extract of Pomegranate Peel (Punica granatum) and Veratrum (Veratrum album) on Oxidative Status, Immunity and Digestive Enzyme Activity in Rainbow Trout (Oncorhynchus mykiss) - Adem Yavuz Sönmez; Soner Bilen; Keriman Yürüten Özdemir; Kerem Alagöz; Halil Özçelik (Journal of Agricultural Sciences)
Aqueous methanolic extracts of pomegranate peel (Punica granatum) and veratrum (Veratrum album) were evaluated for their effects of supplementation in fish diets on oxidative status, digestive enzymes and immunity of rainbow trout fingerlings (Oncorhynchus mykiss). Three different concentrations of pomegranate 250 (P250), 500 (P500) and 1000 (P1000) mg kg-1 and veratrum 250 (V250), 500 (V500) and 1000 (V1000) mg kg-1 were added to the diet and the fish were fed these diets for 60 days over a control diet without any supplementation (P0 and V0, respectively). Immune responses and oxidative status of fish were evaluated every 20 days. Digestive enzyme activity and growth performances were determined at the end of study. We observed that the respiratory burst activity significantly increased (P<0.05) at the end of the study compared to control except in the V500 fish group. Lysozyme was increased on the 20th and 40th day of the study in all experimental groups compared to the control group (P<0.05). Myeloperoxidase activity was observed to increase on the 40th day in veratrum treated groups and significantly decreased (P<0.05) on the 60th day in all groups compared to the control. Haematological responses showed a declining trend in all the groups supplemented with veratrum extract. SOD activity increased in pomegranate groups while no differences were observed on catalase activity. G6PDH activity was observed to decline in the veratrum groups, however, GPx activity significantly increased (P<0.05) in V500 and V100 groups. Lipid peroxidation was determined at the lowest level on the 20th and 40th days of the study in P1000 and V250 fish groups. The study indicated a positive impact of pomegranate peel extract on the immunity of rainbow trout at moderate doses of supplementation.